2015
DOI: 10.1002/jrs.4765
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism responsible of Raman enhancement on carbon allotropes surfaces: the role of molecule‐surface vibrational coupling in SERS

Abstract: The ability of different carbon allotropes surfaces as potential substrates for enhanced Raman spectroscopy is analysed theoretically and the factors responsible of the Raman-enhancing mechanism deeply scrutinised. Our analysis is based on the partition of the Raman tensor into molecule and surface terms, which leads to three different contributions to the Raman activity ('molecule', 'surface' and 'intermolecular'). Both static and pre-resonance conditions are considered in our analysis of the Raman spectra of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…These EFs may certainly lead to Raman and Hyper-Raman enhancements on the line of electromagnetic enhancements produced by metallic nanoparticles. In fact, this result was theoretically verified, only for Raman scattering, in isolated carbon nanodisks [26,27]. Calculations of the Raman spectra reflected EFs around 10 8 using on-resonance conditions.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…These EFs may certainly lead to Raman and Hyper-Raman enhancements on the line of electromagnetic enhancements produced by metallic nanoparticles. In fact, this result was theoretically verified, only for Raman scattering, in isolated carbon nanodisks [26,27]. Calculations of the Raman spectra reflected EFs around 10 8 using on-resonance conditions.…”
Section: Resultsmentioning
confidence: 85%
“…Thus, contrary to extended graphene sheets, these resonances do not correspond to charge transfer excitations but electronic excitations involving surface electrons. In the case of isolated graphene nanodisks and upon on-resonance conditions, surface electronic excitations were found to lead to strong Raman enhancements of adsorbed molecules such as pyridine, porphyrin or phthalocyanine [26,27]. However, the ground-to-excited state electron deformations indicate the strong resonances are not localized within the carbon nanodisk but within the outer carbon structure in C24BN and C54BN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under pre‐resonance conditions, the surface contributes significantly to the Raman activity of the pyridine vibrational modes, even if the electronic transition involves exclusively energy levels from the surface. This is because of small vibrational couplings between molecule and surface modes which are negligible in metallic surface‐like silver . Sloufova et al .…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…This is because of small vibrational couplings between molecule and surface modes which are negligible in metallic surface-like silver. [25] Sloufova et al have identified two Ag-2,2′:6′,2″-terpyridine (tpy) surface species on Ag nanoparticle surfaces by excitation wavelength dependence of SERS spectra and factor analysis which provides evidence for the chemical mechanism contribution to SERS of Ag(0)-tpy. [26] Applications of SERS Caglayan and co-workers have described two SERS-based assays for the sensitive detection of modafinil in urine matrix.…”
Section: Theoretical Aspects Of Sers Enhancementmentioning
confidence: 99%